2011
DOI: 10.4028/www.scientific.net/amr.183-185.466
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Phosphorus Adsorption of Aerated Concrete in Wastewater Treatment

Abstract: Constructed wetlands are widely used throughout the world to treat a wide variety of wastewater. Numerous researches on phosphorus removal have been reported, however, in practice, phosphorus removal efficiency through the constructed wetland is still relatively lower due to various reasons. In this paper, the phosphorus adsorption capacity of aerated concrete (a building material) was investigated by using Freundlich and Langmuir adsorption isotherm equations, and then the possibility, using aerated concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
1
1
Order By: Relevance
“…Cucarella and Renman (2009) emphasised that high solute concentrations encourage other adsorption mechanisms, such as substantial boundary concentrations; Zhang highlighted that the P adsorption of a filler is only attributed to the physical adsorption in low P concentration water, while the high P concentration of the water can sufficiently cause chemical reactions, such as complexation and precipitation, with the metals (Zhang et al 2005). In addition, some works have reported that the equilibrium adsorption capacity of aerated concrete for phosphorus reaches 300-6064 mg/kg, which is much higher than the amount of the P adsorption obtained in the present study (Fu & Li 2011;Deng & Wheatley 2018;Zhang & Zhu 2018;Castellar et al 2019). The results of the above studies were mainly due to them being based on kinetic bath studies of aerated concrete, which was crushed into a powder and then placed in extremely high P concentration water (5-60 mg/L), and the gained equilibrium adsorption capacity was nearly the theoretical maximum.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…Cucarella and Renman (2009) emphasised that high solute concentrations encourage other adsorption mechanisms, such as substantial boundary concentrations; Zhang highlighted that the P adsorption of a filler is only attributed to the physical adsorption in low P concentration water, while the high P concentration of the water can sufficiently cause chemical reactions, such as complexation and precipitation, with the metals (Zhang et al 2005). In addition, some works have reported that the equilibrium adsorption capacity of aerated concrete for phosphorus reaches 300-6064 mg/kg, which is much higher than the amount of the P adsorption obtained in the present study (Fu & Li 2011;Deng & Wheatley 2018;Zhang & Zhu 2018;Castellar et al 2019). The results of the above studies were mainly due to them being based on kinetic bath studies of aerated concrete, which was crushed into a powder and then placed in extremely high P concentration water (5-60 mg/L), and the gained equilibrium adsorption capacity was nearly the theoretical maximum.…”
Section: Resultscontrasting
confidence: 84%
“…Therefore, aerated concrete is widely used in sewage treatment. The theoretical maximum adsorption amount of aerated concrete reportedly reaches 6 064 mg/kg (Fu & Li 2011). Considering the adsorption-desorption characteristics of fillers, the possibility of using aerated concrete as a filler to reduce the instantaneous P peak value of the drainage water in the initial stage of rainfall was explored by studying the adsorption and desorption properties of the aerated concrete separately.…”
mentioning
confidence: 99%